Emergencies in The Maritime Field A Literatur Review - Rian Pramudya; Salsabila, Rika Kamila; Kamilah, Nilam Nurmilatun; Putri, Atina Rizki; Pramudia, Prananda Rizki; Saraswati, Ni Wayan Citra Ayu; Amatullah, Tazkiyah Arafah; Hunaifi, Ilsa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Indonesia is the largest archipelagic country in the world, with extensive coastal and oceanic areas and a high diversity of marine biodiversity. The coastal regions of Indonesia serve as habitats for various types of marine animals that possess both beauty and potential dangers, particularly from marine animal stings. In addition to marine animal stings, decompression sickness also poses a serious emergency in the maritime context. The purpose of this article is to provide new insights into the importance of understanding and recognizing decompression syndrome, as well as the bites and stings caused by marine animals, as early indicators of emergencies in the maritime field. This understanding can enhance early detection, appropriate treatment, and awareness of complications arising from maritime emergencies. The article will focus on marine animals such as the blue-ringed octopus, sea urchins, pufferfish, lionfish, jellyfish, stingrays, and stonefish, which are associated with emergencies in the maritime field. Data sources were gathered through electronic searches on library databases including Google Scholar, ProQuest, MDPI, and PubMed to find articles discussing